2012
DOI: 10.2176/nmc.52.714
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Benign Cavernous Sinus Tumors: Treatment Concept and Outcomes in 120 Cases

Abstract: Availability of modern computer-aided robotized devices, such as the Automatic Positioning System (APS TM ; Elekta Instruments AB, Stockholm, Sweden) and Perfexion TM (Elekta Instruments AB), allowed us to develop the original concept of robotic gamma knife microradiosurgery, which is based on the very precise irradiation of the lesion with regard to conformity and selectivity; intentional avoidance of the excessive irradiation of functionally-important anatomical structures, particularly cranial nerves, locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Based on the published literature, surgeryrelated morbidity for CSM was higher than that for stereotactic radiosurgery (SRS), including either gross total and subtotal resection. Patients receiving SRS experienced lower rates of tumor recurrence compared with patients who underwent surgery alone [4,7]. Long-term studies of meningioma involving the cavernous sinus after surgery reported recurrence rates of 9.6 % after complete resection and 15.2 % after subtotal resection [6,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the published literature, surgeryrelated morbidity for CSM was higher than that for stereotactic radiosurgery (SRS), including either gross total and subtotal resection. Patients receiving SRS experienced lower rates of tumor recurrence compared with patients who underwent surgery alone [4,7]. Long-term studies of meningioma involving the cavernous sinus after surgery reported recurrence rates of 9.6 % after complete resection and 15.2 % after subtotal resection [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, application of SRS, particularly GKS to cavernous sinus meningioma, has been generally accepted as the primary treatment of tumors < 3 cm in greatest dimension, not significantly compromising the optic pathway. Larger tumors >3 cm in maximum diameters or those with marked optic pathway compression benefits surgical debulking and optic nerve decompression followed by adjunctive Gamma Knife surgery (GKS) for residual or fractionated stereotactic radiosurgery or radiotherapy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The conventional goal of GKS is achieving tumor growth control, and reducing the mass volume is important to restore nerve function particularly related to direct compression of the cranial nerves. 18 Single-session GKS is more effective for small or medium-sized CSCHs than for larger tumors. Hypofractionated SRT using CyberKnife has been used for primary or postoperative management of patients with CSCHs with favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas remain adherent to surrounding structures, bone, dura, sinuses, and the carotid wall, reducing the possibility of achieving complete surgical resection. Postoperative morbidity in cases of cavernous sinus tumors, particularly related to dysfunction of the CN, varies from 18% up to 63% [5,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%